Agricultural Irrigation Using Treated Wastewater: Challenges and Opportunities - Obijianya, Christian C.; Yakamercan, Elif; Karimi, Mahmoud; Veluru, Sridevi; Simko, Ivan; Eshkabilov, Sulaymon; Simsek, Halis (Mdpi, 2025)
Reusing and recycling treated wastewater is a sustainable approach to meet the growing demand for clean water, ensuring its availability for both current and future generations. Wastewater can be treated in such advanced ways that it can be used for industrial operations, recharging groundwater, irrigation of fields, or even manufacturing drinkable water. This strategy meets growing water demand in water-scarce areas while protecting natural ecosystems. Treated wastewater is both a resource and a challenge. Though it may be nutrient-rich and can increase agricultural output while showing resource reuse and environmental conservation, high treatment costs, public acceptance, and contamination hazards limit its use. Proper treatment can reduce these hazards, safeguarding human health and the environment while enhancing its benefits, including a stable water supply, nutrient-rich irrigation, higher crop yields, economic development, and community resilience. On the one hand, inadequate treatment may lead to soil salinization, environmental degradation, and hazardous foods. Examining the dual benefits and risks of using treated wastewater for agricultural irrigation, this paper investigates the complexities of its use as a valuable resource and as a potential hazard. Modern treatment technologies are needed to address these difficulties and to ensure safe and sustainable use. If properly handled, treated wastewater reuse has enormous potential for reducing water scarcity and expanding sustainable agriculture as well as global food security.
Keywords: treated wastewater; agricultural irrigation; environmental benefits